Nanometer seed crystal additive for UHPC (Ultra High Performance Concrete) and preparation method of nanometer seed crystal additive

By dispersing fibrous magnesium phosphate nanocrystals with nanoCO2 bubbles in UHPC, promoting hydration reactions and improving the compactness and toughness of UHPC, the problem of UHPC breaking during impact or overload is solved, and material cost and carbon footprint are reduced.

CN119797805AActive Publication Date: 2025-04-11JIANGSU CHINA RAILWAY ARIT NEW MATEIRALS CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510307312.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-11
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

UHPC is prone to sudden fracture when subjected to external impact or overload, lacks plastic deformation capabilities, and its high gelling material usage leads to a significant increase in material costs and carbon footprint, limiting its promotion and application in modern construction projects.

Method used

NanoCO2 bubbles are used to disperse fibrous magnesium phosphate nanocrystals, and the nanobubbles are rapidly ruptured in the cement mixture. The released carbon dioxide reacts with calcium hydroxide to form nanocalcium carbonate crystals. As the crystal nucleus of the hydration reaction, it significantly promotes the precipitation and growth of the hydration products, accelerates the hydration process, and improves the compactness and toughness of UHPC through the magnesium phosphate nanocrystals and nanocalcium carbonate.

Benefits of technology

It significantly improves the early strength and toughness of UHPC, shortens the mold maintenance time, improves mold turnover and construction efficiency, while reducing the viscosity and cost of the material, and reduces the carbon footprint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a nanocrystal seed additive for UHPC (Ultra High Performance Concrete) and a preparation method of the nanocrystal seed additive, and relates to the field of new concrete materials. The additive consists of nano CO2 bubbles, fibrous magnesium phosphate nanocrystals and a bubble stabilizer, the particle size of the nano bubbles is 50-200nm, and the volume ratio of the nano bubbles is 30-60%; the length-diameter ratio of the nanocrystalline is 5-10, and the size of the nanocrystalline is 10-20 nm; the nano bubbles, the magnesium phosphate nanocrystals and the bubble stabilizer are mutually filled in different scales to form a multi-scale and multi-phase suspension aqueous solution. In the additive, magnesium phosphate nanocrystals are dispersed by nano bubbles, so that shielding of a chemical dispersing agent on active sites on the surface of a seed crystal is avoided; carbon dioxide released by rapid fracture of the nano bubbles in the cement mixture reacts with calcium hydroxide to generate nano calcium carbonate crystals as hydration reaction crystal nucleuses, and precipitation growth of hydration products is promoted to accelerate hydration; the fibrous magnesium phosphate nanocrystalline seed effectively enhances the toughness and tensile strength of the UHPC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional new materials for concrete, and in particular to a nanocrystalline seed additive for UHPC and a preparation method thereof. Background Art

[0002] As a new type of high-strength and high-durability building material, UHPC has attracted much attention in the field of civil engineering in recent years. UHPC has ultra-high compressive strength (usually more than 150 MPa), excellent toughness and durability, as well as good freeze-thaw resistance and chemical corrosion resistance. These excellent properties make UHPC have broad application prospects in bridges, super high-rise buildings, marine engineering and other fields, and can effectively improve the safety and service life of the structure.

[0003] Although ultra-high performance concrete (UHPC) has shown excellent performance in terms of strength and durability, there are still some problems in practical application. Due to its dense microstructure and lack of sufficient crack bridging and energy absorption mechanisms, UHPC is more prone to sudden fracture and lacks plastic deformation capacity when subjected to external impact or overload. At present, 1-2% steel fiber is often added by volume to improve its ductility, but this increases the construction cost of UHPC exponentially. In addition, the mix ratio of UHPC contains a large amount of cementitious materials such as cement, silica fume and mineral powder. The high amount of cementitious materials not only increases the material cost, but also leads to a significant increase in its carbon footprint. This is contrary to the green building and sustainable development goals advocated globally, and limits the promotion and application of UHPC in modern construction projects that pursue low-carbon and environmental protection.

[0004] With the development of nanotechnology, researchers have tried to use nanomaterials in the production of UHPC. Because nanomaterials have the characteristics of fine particles, large specific surface area, and high activity, they can fill micropores in UHPC, promote hydration reactions, and improve the performance of the interface transition zone. Chinese patent CN116283043A provides an ultra-early strength admixture for UHPC prefabricated components and a preparation method thereof. This patented technology uses reactive ball milling technology to grind industrial solid waste with active grinding aids, inactive grinding aids, and nanomaterials (such as nano calcium carbonate, nano silicon dioxide, and nano aluminum oxide) to change the chemical properties of the surface of solid waste particles, increase their reactivity, and use them in conjunction with accelerators and retarders to increase the early strength of UHPC while reducing its viscosity, improving fluidity, and reducing early self-shrinkage. Chinese patent CN113416046A discloses an ultra-high performance concrete for orthogonal special-shaped steel bridge deck paving. This technology uses modified highly thixotropic nano calcium carbonate to fill the gap between cement and admixtures, displace the free water in the adhesive system, reduce the thickness of the water film, reduce the viscosity of the UHPC slurry, and at the same time improve the density of the matrix and increase the strength. Chinese patent CN111018394A The present invention provides a nanocrystalline core material for UHPC prefabricated components and its preparation and application methods. The nanocrystalline core material (nanohydrated calcium silicate) for preparing UHPC prefabricated components is added to ultra-high performance concrete to effectively improve the fluidity of its mixture; significantly improve the early strength of ultra-high performance concrete, greatly shorten the mold maintenance time of UHPC prefabricated components, and improve mold turnover and construction efficiency. Chinese patent CN117886529B discloses a mineral admixture that improves the mixing efficiency of ultra-high performance concrete. By compounding fly ash, calcium carbonate powder, and nanoparticles (silica ash and titanium powder), and rationally controlling the specific composition of fly ash and calcium carbonate powder, the mineral admixture can shorten the slurry discharge time by 20% to 88% after being applied to UHPC, greatly improving the mixing efficiency of UHPC. It can also reduce the viscosity of the UHPC mixture by more than 20% and increase the 28d compressive strength by 1% to 10%, thereby achieving a comprehensive improvement in the preparation efficiency, construction performance, and mechanical properties of ultra-high performance concrete.

[0005] From the existing public technology, many nanomaterials (such as silica fume, nano alumina, nano SiO2, nano CaCO3, nano hydrated calcium silicate) are used to improve the working performance of UHPC mixtures and improve the density of hardened UHPC, thereby improving the compressive strength of UHPC. There are few reports on the use of nanomaterials to achieve the simultaneous strengthening and toughening of UHPC. In addition, although the nano seed technology can induce crystal growth on the surface of ordinary concrete, in the UHPC system, due to the serious lattice mismatch between the hydration product and the crystallization phase, the early strength improvement shown by the existing technology is not obvious. Summary of the invention

[0006] 1. Technical problems to be solved: In view of the above technical problems, the present invention provides a nanocrystalline seed additive for UHPC and a preparation method thereof. In the additive, small molecules, nanocrystals and nanobubbles of different scales are mutually filled, and the three phases of gas, liquid and solid cooperate with each other to form a stable multi-scale multi-phase suspended aqueous solution. At the same time, the nanocrystalline seed additive for UHPC uses nano CO2 bubbles to disperse fibrous magnesium phosphate nanocrystals, avoiding the shielding of the surface active sites of the seed by chemical dispersants. The nanobubbles quickly burst in the cement mixture, and the released carbon dioxide reacts with calcium hydroxide to form nano-calcium carbonate crystals. These crystals serve as the nuclei of the hydration reaction, significantly promoting the precipitation and growth of the hydration products and accelerating the hydration process. The fibrous magnesium phosphate nanocrystals and nano-calcium carbonate cooperate to improve the density and toughness of UHPC.

[0007] 2. Technical solution: A nanocrystalline seed additive for UHPC, the additive consists of nano CO2 bubbles, fibrous magnesium phosphate nanocrystals and a bubble stabilizer, wherein the magnesium phosphate nanocrystals serve as the crystal nuclei of cement materials during cement hydration reaction; wherein the particle size of the nano CO2 bubbles is 50-200 nm, and the volume accounts for 30-60% of the total volume; the magnesium phosphate nanocrystals have an aspect ratio of 5-10 and a particle size of 10-20 nm; the bubble stabilizer is a composite of an inorganic salt electrolyte and an organic surfactant molecule; the nano CO2 bubbles, the magnesium phosphate nanocrystals and the bubble stabilizer are mutually filled at different scales to form a stable multi-scale multi-phase suspended aqueous solution.

[0008] A method for preparing a nanocrystalline seed additive for UHPC comprises the following steps: Step 1: Preparation of fibrous magnesium phosphate nanocrystal suspension: Weigh 35-50 parts by mass of soluble magnesium salt and dissolve it in 500 parts by mass of deionized water to prepare a magnesium salt solution; then weigh 16.7 parts by mass of 0.1-0.6 parts of a polymer modifier are added, and the solution is stirred until the solution is completely transparent to prepare a phosphate solution; then, the phosphate solution is slowly dripped into the magnesium salt solution by a constant flow pump, and the pH value of the solution is adjusted to 8-10 in real time using a 1M ammonia solution, and a milky suspension gradually appears in the solution, indicating that fibrous magnesium phosphate nanocrystals are formed; after the dropwise addition is completed, stirring is continued for 30-120 minutes; then, the reaction solution is transferred to a centrifuge tube, centrifuged at a speed of 6000-8000 rpm for 10-15 minutes to separate the precipitate, and washed with deionized water for 3-5 times to remove residual impurities and unreacted products; 51.8-88.5 parts of the washed fibrous magnesium phosphate nanocrystals are redispersed in 500 parts of deionized water, and 0.1-0.3 parts of a stabilizer are added, and a fibrous magnesium phosphate nanocrystal suspension is obtained by ultrasonic-assisted dispersion technology.

[0009] Step 2: Using a microfluidic device, 0.1 to 3 parts by mass of nano carbon dioxide bubbles are uniformly dispersed in the suspension obtained in step 1; CO2 gas is stably supplied to the gas phase inlet of the microfluidic device through a pressure reducing valve and a flow meter, at which time the gas pressure of the pressure reducing valve is 0.1 to 0.5 MPa, and the flow rate of the flow meter is set to 0.5 to 1 L / min; at the same time, the suspension obtained in step 1 is injected into the liquid phase inlet of the microfluidic device through a liquid injection module at a flow rate of 10 to 20 mL / min; at the outlet nanonozzle of the microfluidic device, the carbon dioxide gas is sheared into nanobubbles with a diameter of 50 to 200 nm and uniformly dispersed in the suspension.

[0010] Step 3: Enhance the stability of nanobubbles; add 0.02-0.05 parts by mass of an inorganic salt electrolyte and 0.02-0.05 parts by mass of a surfactant to the suspension generated in step 2 and stir gently to form a stable protective film on the bubble surface, enhance the interface stability of the bubble, and then obtain the target UHPC nanocrystal seed additive.

[0011] Furthermore, the soluble magnesium salt is one or a combination of more than one of magnesium sulfate, magnesium chloride, magnesium carbonate, magnesium nitrate, magnesium acetate and magnesium citrate.

[0012] Furthermore, the soluble phosphoric acid is one or a combination of more than one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, trisodium phosphate, tripotassium phosphate, ammonium phosphate, and ammonium hydrogen phosphate.

[0013] Furthermore, the polymer modifier is a combination of polyethylene glycol with a molecular weight of 2000-8000 and polyvinyl alcohol with a molecular weight of 500-3000 in any proportion.

[0014] Furthermore, the stabilizer is one or a combination of polyvinyl pyrrolidone with a molecular weight of 8000-15000, sodium polyacrylate with a molecular weight of 30000-50000, and polyacrylamide with a molecular weight of 50000-100000.

[0015] Furthermore, the inorganic salt in the inorganic salt electrolyte is one or a combination of more than one of sodium chloride, potassium chloride, sodium nitrate, sodium nitrite, potassium nitrate and potassium nitrite.

[0016] Furthermore, the surfactant is one or a combination of more than one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyethylene glycol octylphenyl ether, cocamidopropyl betaine, dodecyldimethylalkyldiquaternary ammonium salt, and hexadecylpyridinium chloride.

[0017] Furthermore, in step 1, the ultrasonic assisted dispersion technology is used to make the solution uniform through ultrasound, at which time the frequency of the ultrasound is 40-60 kHz and the processing time is 5-10 minutes.

[0018] 3. Beneficial effects: (1) The nanocrystalline seed additive for UHPC disclosed in this method is the first to use magnesium phosphate nanocrystals as the nucleus of cement materials. Cement hydration products can grow epitaxially on its surface, showing perfect compatibility, which can greatly promote the positive progress of cement hydration. Its application in UHPC can overcome the problem of slow strength development.

[0019] (2) The nanocrystalline seed additive for UHPC disclosed in the present method, wherein the magnesium phosphate nanocrystalline seed is a fibrous nanocrystal that can significantly improve the toughness of UHPC.

[0020] (3) The nano-seed additive for UHPC disclosed in the present method has excellent bonding properties between the magnesium phosphate nano-seeds with a struvite-like structure and cement hydration products, thereby maximizing the pull-out resistance of the nanofibers and significantly improving the tensile strength of UHPC.

[0021] (4) The method discloses a nanocrystalline seed additive for UHPC. The magnesium phosphate nanocrystalline seed additive significantly optimizes the dispersibility of the magnesium phosphate nanocrystalline seeds by introducing nano carbon dioxide bubbles, thereby avoiding the shielding of the active sites on the seed surface by the dispersant, thereby greatly improving its specific surface area and reaction efficiency.

[0022] (5) The nano-seed additive for UHPC disclosed in the method has nano-bubbles that burst rapidly in the cement mixture, and the released carbon dioxide reacts with calcium hydroxide to form nano-calcium carbonate crystals. These crystals serve as crystal nuclei for the hydration reaction, significantly promoting the precipitation and growth of hydration products and accelerating the hydration process.

[0023] (6) The nanocrystalline seed additive for UHPC disclosed in the method, magnesium phosphate nanocrystals and nano-calcium carbonate work together to fill the internal pores of the material through the micro-nano aggregate effect and induce the hydration product to crystallize and grow on the surface, thereby further improving the density and compressive strength of UHPC. DETAILED DESCRIPTION

[0024] The embodiments of the present invention are described in detail below. The embodiments of the present invention are implemented based on the technical solution of the present invention, and detailed implementation methods and operation processes are given. However, the protection scope of the present invention is not limited to the following embodiments.

[0025] Example 1 Weigh 40 parts of magnesium sulfate and dissolve them in 500 parts of deionized water to obtain a soluble magnesium salt solution; take another 25 parts of disodium hydrogen phosphate and dissolve them in 500 parts of deionized water, add 2 parts of a polymer modifier composed of polyethylene glycol with a molecular weight of 4000 and polyvinyl alcohol with a molecular weight of 2000 in a ratio of 1:1, and stir until the solution is transparent. Use a constant flow pump to slowly drip the phosphate solution into the magnesium salt solution within 60 minutes, and adjust the pH value to 9 with 1M ammonia water. The solution gradually appears a milky suspension, indicating that nano magnesium phosphate particles are formed; after the addition is completed, continue stirring for 60 minutes. The reaction solution is transferred to a centrifuge tube, centrifuged at 7000 rpm for 12 minutes, and the precipitate is separated and washed with deionized water 3 times. 60 parts of washed nano magnesium phosphate particles are redispersed in 500 parts of deionized water, 0.2 parts of polyvinyl pyrrolidone with a molecular weight of 10000 are added as a stabilizer, and ultrasonic waves (frequency 50kHz, time 7 minutes) are used to assist dispersion to obtain a nano magnesium phosphate particle suspension. Through the microfluidic device, carbon dioxide gas is supplied at a pressure of 0.3MPa and a flow rate of 0.8L / min, and the suspension is injected into the device at a flow rate of 15mL / min; at the nano nozzle, carbon dioxide is sheared into nanobubbles of about 100nm, and 1.5 parts of nanocarbon dioxide bubbles are evenly dispersed in the suspension. Finally, 0.03 parts of sodium chloride and 0.04 parts of sodium dodecyl sulfate are added and gently stirred to form a stable protective film on the bubble surface, enhance the stability of the bubble interface, and obtain a nanocrystalline seed additive for UHPC.

[0026] Example 2 Weigh 35 parts of magnesium nitrate and dissolve them in 500 parts of deionized water; take another 30 parts of ammonium dihydrogen phosphate and dissolve them in 500 parts of deionized water, add 5 parts of polyvinyl alcohol with a molecular weight of 2500, and stir until the solution is transparent. Use a constant flow pump to drip the phosphate solution into the magnesium salt solution within 90 minutes, and adjust the pH value to 8.5 with 1M ammonia water to form a milky suspension; after the addition is completed, continue stirring for 90 minutes. Centrifuge the reaction solution at 6000 rpm for 15 minutes and wash the precipitate 4 times. Redisperse 65 parts of the particles in 500 parts of deionized water, add 0.1 parts of sodium polyacrylate with a molecular weight of 40000 as a stabilizer, and ultrasonically disperse (45kHz, 8 minutes) to obtain a suspension. Through a microfluidic device, carbon dioxide gas is supplied at a pressure of 0.2MPa and a flow rate of 0.6L / min, and the suspension is injected at a flow rate of 12mL / min; nanobubbles with a diameter of about 150nm are generated, and 1 part of nano carbon dioxide bubbles are evenly dispersed in the suspension. Finally, 0.05 parts of potassium nitrate and 0.03 parts of hexadecyltrimethylammonium bromide were added and stirred to form a protective film to obtain a nanocrystalline seed additive for UHPC.

[0027] Example 3 Weigh 45 parts of magnesium acetate and dissolve them in 500 parts of deionized water; take another 20 parts of trisodium phosphate and dissolve them in 500 parts of deionized water, add 4 parts of polyethylene glycol with a molecular weight of 6000, and stir until the solution is transparent. Add the phosphate solution dropwise to the magnesium salt solution within 45 minutes, and maintain the pH value at 9.5 with 1M ammonia water to form a milky suspension; after the addition is completed, continue stirring for 30 minutes. Centrifuge the reaction solution at 8000 rpm for 10 minutes and wash the precipitate 5 times. Redisperse 67 parts of the particles in 500 parts of deionized water, add 0.3 parts of polyacrylamide with a molecular weight of 80000 as a stabilizer, and ultrasonically disperse (55kHz, 5 minutes) to obtain a suspension. Through a microfluidic device, carbon dioxide gas is supplied at a pressure of 0.5MPa and a flow rate of 1L / min, and the suspension is injected at a flow rate of 20mL / min; nanobubbles with a diameter of about 50nm are generated, and 3 parts of nano carbon dioxide bubbles are evenly dispersed in the suspension. Finally, 0.02 parts of sodium nitrite and 0.05 parts of polyethylene glycol octylphenyl ether were added to form a stable protective film to obtain a nanocrystalline seed additive for UHPC.

[0028] Example 4 Weigh 50 parts of magnesium citrate and dissolve them in 500 parts of deionized water; take another 16.7 parts of potassium dihydrogen phosphate and dissolve them in 500 parts of deionized water, add 6 parts of a polymer modifier composed of polyethylene glycol with a molecular weight of 8000 and polyvinyl alcohol with a molecular weight of 3000 in a ratio of 2:1, and stir until the solution is transparent. Add the phosphate solution dropwise to the magnesium salt solution within 75 minutes, adjust the pH value to 10 with 1M ammonia water, and form a milky suspension; after the addition is completed, continue stirring for 120 minutes. Centrifuge the reaction solution at 7500 rpm for 10 minutes, and wash the precipitate 3 times. Redisperse 68.5 parts of the particles in 500 parts of deionized water, add 0.1 parts of polyvinyl pyrrolidone with a molecular weight of 12000 as a stabilizer, and obtain a suspension by ultrasonic dispersion (60kHz, 10 minutes). Through the microfluidic device, carbon dioxide gas was supplied at a pressure of 0.4MPa and a flow rate of 0.9L / min, and the suspension was injected at a flow rate of 18mL / min; nanobubbles with a diameter of about 75nm were generated, and 2 parts of nano carbon dioxide bubbles were evenly dispersed in the suspension. Finally, 0.04 parts of potassium chloride and 0.02 parts of cocamidopropyl betaine were added and stirred to form a protective film to obtain a nanocrystalline seed additive for UHPC.

[0029] Example 5 Weigh 37 parts of magnesium carbonate and dissolve them in 500 parts of deionized water; take another 32.5 parts of ammonium phosphate and dissolve them in 500 parts of deionized water, add 0.1 parts of polyvinyl alcohol with a molecular weight of 3000, and stir until the solution is transparent. Add the phosphate solution to the magnesium salt solution within 30 minutes, adjust the pH value to 8 with 1M ammonia water, and form a milky suspension; after the addition is completed, continue stirring for 30 minutes. Centrifuge the reaction solution at 8000 rpm for 15 minutes, and wash the precipitate 5 times. Redisperse 51.8 parts of particles in 500 parts of deionized water, add 0.3 parts of sodium polyacrylate with a molecular weight of 35000 as a stabilizer, and ultrasonically disperse (40kHz, 5 minutes) to obtain a suspension. Through a microfluidic device, carbon dioxide gas is supplied at a pressure of 0.1MPa and a flow rate of 0.5L / min, and the suspension is injected at a flow rate of 10mL / min; nanobubbles with a diameter of about 200nm are generated, and 0.1 parts of nano carbon dioxide bubbles are evenly dispersed in the suspension. Finally, 0.02 parts of potassium nitrite and 0.05 parts of cetylpyridinium chloride were added and gently stirred to form a stable protective film, and finally a nanocrystalline seed additive for UHPC was obtained.

[0030] Test Example 1: Hydration Promotion The test was conducted using the UHPC mixture ratio, which was as follows: Portland cement (P.Ⅰ.52.5): 800 kg / m³ Silica fume: 200 kg / m³ Quartz sand (particle size 0.15-0.6 mm): 1020 kg / m³ Quartz powder (particle size less than 0.15 mm): 200 kg / m³ Water: 160 kg / m³ High-efficiency water reducing agent: 24 kg / m³ (about 2% of the total amount of cementitious materials) Steel fiber: 156 kg / m³ (length 13 mm, diameter 0.2 mm) The setting time, 12h compressive strength and 1d compressive strength were used to characterize the hydration promotion effect of different nano-seed additives on UHPC. Control group 1 used a nano-hydrated calcium silicate type seed additive from a certain manufacturer on the market, and control group 2 used a nano-calcium carbonate type seed additive from a certain manufacturer on the market. The dosage of the nano-seed additive was 1% of the cement mass, and the benchmark cement was used for the experiment, which was cured under standard curing conditions. The test results are shown in Table 1.

[0031] Table 1. Effect of nanocrystalline seed additives on the hydration process of UHPC

[0032] As can be seen from Table 1, Examples 1 to 5 have almost no negative effect on the fluidity and operability of the UHPC mixture, while the control group 2 significantly reduces the fluidity of the UHPC mixture. Adding 1% nanocrystalline seed additive not only effectively shortens the initial and final setting times, accelerates the setting speed of concrete, but also greatly improves the early compressive strength, so that UHPC can reach a high strength level in a short time. In contrast, the setting time of the control group and the blank group is longer, the early strength development is slow, and even fails to harden within 12 hours. It can be seen that the nanocrystalline seed additive for UHPC of the present invention has a significant promoting effect on the hydration reaction of UHPC.

[0033] Test Example 2: Mechanical Properties Test The UHPC mixture was prepared according to the mix ratio described in Test Example 1, and the time molding and curing were carried out according to the relevant provisions of 3.3 in T / CECS 864-2021 "Ultra-High Performance Concrete Test Method Standard", and the compressive strength, flexural strength and compressive strength tests were carried out according to the relevant provisions of 5.1, 5.5 and 5.6. The test results are shown in Table 2.

[0034] Table 2. Effect of nanocrystalline seed additives on the mechanical properties of UHPC

[0035] According to the results in Table 2, the 28-day compressive strength of the UHPC specimens doped with the nanocrystalline seed additives described in Examples 1 to 5 is between 172.2 MPa and 179.2 MPa, with an average of about 176.8 MPa, which is significantly higher than the blank group; the 28-day flexural strength is between 39.5 MPa and 42.8 MPa, which is about 20% higher than the blank group; the 8-day tensile strength has also been greatly improved. In comparison, the 28-day compressive strength, 28-day flexural strength, and 28-day tensile strength of the UHPC specimens doped with the nanocrystalline seed additives of the control group 1 and the control group 2 did not show a significant improvement compared with the blank group. These data clearly show that the nanocrystalline seed additives for UHPC in this scheme have excellent effects in enhancing the compressive, flexural and tensile properties of UHPC.

[0036] Although the present invention has been disclosed as above in terms of preferred embodiments, they are not intended to limit the present invention. Anyone skilled in the art can make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection defined by the claims of this application.

Claims

1. A nanocrystalline seed additive for UHPC, characterized in that: The additive consists of nano CO2 bubbles, fibrous magnesium phosphate nanocrystals and bubble stabilizers. The magnesium phosphate nanocrystals serve as the crystal nuclei of cement materials during cement hydration reaction. The particle size of the nano CO2 bubbles is 50-200nm, and the volume accounts for 30-60% of the total volume. The magnesium phosphate nanocrystals have an aspect ratio of 5-10 and a particle size of 10-20nm. The bubble stabilizer is a composite of inorganic salt electrolytes and organic surfactant molecules. Nano CO2 bubbles, magnesium phosphate nanocrystals and bubble stabilizers are filled with each other at different scales to form a stable multi-scale multi-phase suspended aqueous solution.

2. A method for preparing a nanocrystalline seed additive for UHPC, used to prepare the additive according to claim 1, characterized in that: The following steps are involved: Step 1: Preparation of fibrous magnesium phosphate nanocrystal suspension; weigh 35-50 parts by mass of soluble magnesium salt and dissolve them in 500 parts by mass of deionized water to prepare a magnesium salt solution; then, weigh 16.7-32.5 parts by mass of soluble phosphate and dissolve them in 500 parts by mass of deionized water, and add 0.1-6 parts by mass of polymer modifier, and stir until the solution is completely transparent to prepare a phosphate solution; then, slowly drip the phosphate solution into the magnesium salt solution through a constant flow pump, and use 1M ammonia solution to adjust the pH value of the solution to 8-10 in real time, and the solution gradually becomes a milky white suspension, indicating that fibrous magnesium phosphate nanocrystals are formed; after the addition is completed, continue stirring for 30-120 minutes; Subsequently, the reaction solution was transferred to a centrifuge tube, centrifuged at 6000-8000 rpm for 10-15 minutes to separate the precipitate, and washed with deionized water 3-5 times to remove residual impurities and unreacted products; Re-dispersing 51.8-88.5 parts by weight of washed fibrous magnesium phosphate nanocrystals in 500 parts by weight of deionized water, adding 0.1-0.3 parts by weight of a stabilizer, and using an ultrasonic-assisted dispersion technique to obtain a fibrous magnesium phosphate nanocrystal suspension; Step 2: using a microfluidic device, evenly dispersing 0.1 to 3 parts by mass of nano carbon dioxide bubbles in the suspension obtained in step 1; stably supplying CO2 gas to the gas phase inlet of the microfluidic device through a pressure reducing valve and a flow meter, at which time the gas pressure of the pressure reducing valve is 0.1 to 0.5 MPa, and the flow rate of the flow meter is set to 0.5 to 1 L / min; at the same time, injecting the suspension obtained in step 1 into the liquid phase inlet of the microfluidic device through a liquid injection module at a flow rate of 10 to 20 mL / min; at the outlet nanonozzle of the microfluidic device, the carbon dioxide gas is sheared into nanobubbles with a diameter of 50 to 200 nm, which are evenly dispersed in the suspension; Step 3: Enhance the stability of nanobubbles; add 0.02-0.05 parts by mass of an inorganic salt electrolyte and 0.02-0.05 parts by mass of a surfactant to the suspension generated in step 2 and stir gently to form a stable protective film on the bubble surface, enhance the interface stability of the bubble, and then obtain the target UHPC nanocrystal seed additive.

3. The method for preparing a nanocrystalline seed additive for UHPC according to claim 2, characterized in that: The soluble magnesium salt is one or a combination of more than one of magnesium sulfate, magnesium chloride, magnesium carbonate, magnesium nitrate, magnesium acetate and magnesium citrate.

4. The method for preparing a nanocrystalline seed additive for UHPC according to claim 2, characterized in that: The soluble phosphoric acid is one or a combination of sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, trisodium phosphate, tripotassium phosphate, ammonium phosphate, and ammonium hydrogen phosphate.

5. The method for preparing a nanocrystalline seed additive for UHPC according to claim 2, characterized in that: The polymer modifier is a combination of polyethylene glycol with a molecular weight of 2000-8000 and polyvinyl alcohol with a molecular weight of 500-3000 in any proportion.

6. The method for preparing a nanocrystalline seed additive for UHPC according to claim 2, characterized in that: The stabilizer is one or a combination of polyvinyl pyrrolidone with a molecular weight of 8000-15000, sodium polyacrylate with a molecular weight of 30000-50000, and polyacrylamide with a molecular weight of 50000-100000.

7. The method for preparing a nanocrystalline seed additive for UHPC according to claim 2, characterized in that: The inorganic salt in the inorganic salt electrolyte is one or a combination of more than one of sodium chloride, potassium chloride, sodium nitrate, sodium nitrite, potassium nitrate and potassium nitrite.

8. The method for preparing a nanocrystalline seed additive for UHPC according to claim 2, characterized in that: The surfactant is one or a combination of the following: sodium lauryl sulfate, hexadecyltrimethylammonium bromide, polyethylene glycol octylphenyl ether, cocamidopropyl betaine, dodecyldimethylalkyldiquaternary ammonium salt, and hexadecylpyridinium chloride.

9. The method for preparing a nanocrystalline seed additive for UHPC according to claim 2, characterized in that: In step 1, the ultrasonic assisted dispersion technology is to make the solution uniform through ultrasound, at which time the frequency of the ultrasound is 40-60 kHz and the processing time is 5-10 minutes.

Citation Information

Patent Citations

  • Ultra-high performance concrete for paving orthogonal special-shaped steel bridge deck

    CN113416046A

  • Super-early-strength admixture for UHPC prefabricated part and preparation method of super-early-strength admixture

    CN116283043A

  • Mineral admixture for improving mixing efficiency of ultra-high performance concrete and ultra-high performance concrete using the same

    CN117886529B

  • Nanocrystalline nucleus material for UHPC prefabricated member, preparation method and application method thereof

    CN111018394A

  • Composite material for improving crack resistance of concrete as well as preparation method and application of composite material

    CN114988737A